Epidemiology of bronchopulmonary dysplasia. Issue 3 (17th March 2014) - Jensen, Erik A.; Schmidt, Barbara
<x xml:space="preserve">Abstract</x> Bronchopulmonary dysplasia (BPD) is among the most common and serious sequelae of preterm birth. BPD affects at least one‐quarter of infants born with birth weights less than 1500 g. The incidence of BPD increases with decreasing gestational age and birth weight. Additional important risk factors include intrauterine growth restriction, sepsis, and prolonged exposure to mechanical ventilation and supplemental oxygen. The diagnosis of BPD predicts multiple adverse outcomes including chronic respiratory impairment and neurodevelopmental delay. This review summarizes the diagnostic criteria, incidence, risk factors, and long‐term outcomes of BPD. Birth Defects Research (Part A) 100:145–157, 2014. © 2014 Wiley Periodicals, Inc.